Standardization of artificial diet for the mass rearing of Helicoverpa armigera - Jat, B L; Dahiya, K K; Rolania, K; Yadav, S S (Indian Journal of Plant Protection, 2020)
Experiment was carried out to standardize the artificial diet for mass rearing of Helicoverpa armigera (Hübner) under laboratory conditions. The average length and breadth of egg was 0.51±0.06 mm, 0.46±0.37 mm and 0.52±0.03 mm, 0.48±0.62 on artificial and natural diet. The average length and breadth of first, second, third, fourth and fifth instar larvae was 1.40±0.09 mm, 0.46±0.02 mm and 1.42±0.01 mm, 0.47±0.16 mm and 4.03±0.22 mm, 0.66±0.07 mm and 4.31±0.01 mm, 0.89±0.25 mm and 8.19±0.36 mm, 1.57±0.63 mm, and 10.29±0.72 mm, 1.87±0.91 mm and 18.70±0.44 mm, 2.78±0.040 mm and 20.15±0.03 mm, 3.17±0.55 mm and 26.01±0.19 mm, 4.09±0.39 mm and 27.32±0.027 mm, 5.88±0.69 mm, respectively with the average duration of 2.69±0.32 and 2.54±0.29, 3.77±0.65 and 3.79±0.11, 3.88±0.49 and 3.72±1.23, 5.35±0.55 and 5.72±0.91 and 6.61±0.008, 6.46±1.07 days, respectively on artificial as well as on natural diet. The average length and breadth of adult male and female was 18.01±0.48 mm and 35.09±1.25 mm, 18.51±1.04 mm and 38.11±1.37 mm, 19.00±0.18 mm and 19.10±0.49 mm, 37.75±1.27 mm and 41.23±1.69 mm, respectively. The average pre-oviposition, oviposition and post-oviposition period was 2.52±0.86 and 2.76±0.84 days, 4.93±0.78 and 5.08±0.90 days and 0.65±0.49 and 0.79±0.93 days, respectively. The total life cycle of male and female was 40.50±2.29 and 41.81±1.89 days and 42.59±1.77 and 43.80±1.93 days.